2001
DOI: 10.1161/01.str.32.6.1323
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke Patterns in Patients With Internal Carotid Artery Disease

Abstract: Background and Purpose-Diffusion-weighted (DW) MRI is a sensitive method that facilitates early stroke pattern identification. There are limited data about the influence of stenosis grade on the development of particular stroke patterns in internal carotid artery (ICA) disease. We therefore investigated the lesion patterns on DW MRI in acute stroke patients with ICA disease. Methods-DW MRI was analyzed in 102 consecutive acute stroke patients with different degrees of ipsilateral ICA disease. Patients were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 40 publications
6
104
3
Order By: Relevance
“…The stroke pattern in the present patient is thought to be classified as an atherothrombotic infarction, and it also showed features of acute multiple brain infarction (AMBI) on MRI. AMBIis reported to be often seen in the vertebrobasilar arterial territory and caused by several mechanisms including artery to artery emboli and hemodynamic hypoperfusion (17). The present patient is particularly inter- matous disease.…”
Section: Discussionmentioning
confidence: 64%
“…The stroke pattern in the present patient is thought to be classified as an atherothrombotic infarction, and it also showed features of acute multiple brain infarction (AMBI) on MRI. AMBIis reported to be often seen in the vertebrobasilar arterial territory and caused by several mechanisms including artery to artery emboli and hemodynamic hypoperfusion (17). The present patient is particularly inter- matous disease.…”
Section: Discussionmentioning
confidence: 64%
“…9 Bonati et al showed different DWI lesion patterns in 15 stenotic and 25 occlusive CAD. 6 However, the number of patients was too limited to perform analyses of associations between different degrees of luminal narrowing and DWI lesion presence and patterns.…”
Section: Discussionmentioning
confidence: 98%
“…Stroke patterns on CT or MRI scan were classified in territorial, embolic, and lacunar stroke as well as borderzone infarction (see Figure 1) as implemented earlier. 18 In a subset of patients, those without MRI scan because of contraindications or inconclusive CT findings, stroke localization and pattern were classified as uncertain.…”
Section: Methodsmentioning
confidence: 99%